Post-weaning piglets fed with different levels of fungal mycotoxins and spray-dried porcine plasma have improved weight gain, feed intake and reduced diarrhea incidence - Muller L.K.F.* (2018)
© 2018 Elsevier LtdMycotoxins are responsible for economic losses in the swine production industry, especially during post-weaning, when piglets are physiologically immature. Spray-dried porcine plasma (SDPP), added to pig diets, may help reduce losses due to mycotoxins. This work investigates the effects of SDPP in post-weaning piglets fed with diets containing natural contaminants or with more contaminants (co-contamination by mycotoxins). Fifty-six castrated weaned piglets were used in a randomized 2 (0 and 6% of SDPP) x 2 (natural contamination or co-contamination with mycotoxin) factorial design, with seven experimental units of two piglets each. The natural contaminants were 0.95 μg/kg aflatoxins +450 μg/kg fumonisins. The co-contaminated diet contained 300 μg/kg aflatoxins +8000 μg/kg fumonisins. Animals were fed 15 days with experimental diets. Feed intake, weight gain, feed efficiency, diarrhea incidence, and economic feasibility of SDPP treatement were evaluated in three periods of five days each. There was no interaction (P < 0.05) between mycotoxins levels and SDPP. Feed intake, weight gain and feed efficiency were higher (P < 0.05) in diets supplemented with SDPP. Animals fed with SDPP showed lower (P < 0.05) diarrhea incidence in the 1–10 day and 1–15 day periods. The experimental dose of mycotoxins reduced (P < 0.05) weight gain at 11–15 days. SDPP proved to be economical feasible over the total experimental period (1–15 days). Spray-dried plasma improved weight gain, feed intake and reduced diarrhea incidence in piglets post-weaning, but did not correlate with various levels of mycotoxins.